KHAZANAH SASTRA INDONESIA SEBAGAI SUMBER KEKAYAAN KONTEN BUDAYA DI ZAMAN EKONOMI KREATIF - Koh Young Hun (Faculty of Humanities, Jember University, 2014)
It is a creative economy era and diverse cultural contents. This sector can produce a big added value. Harry Potter shows that a story can take part in the creative economy sector. The British government has chosen the creative industry as one of the policy agendas. Total value added (Gross value added) of the creative industry reaches 5.2 percent of GDP, 8.5 percent of job placement, and 8.0 percent export of the total GDP. Korea also managed to develop a creative industry. Government agencies such as KOCCA have played an important role. In the meantime, the positive image of Korea formed through the Korean Wave and K-Pop provides enough support to introduce the content of Korean culture abroad. Indonesia also has the potential to produce cultural contents because of its richness of stories and Indonesians’ creativity. The potential can be explored and developed as a base to strengthen the development of creative industry. To be implemented and managed, the government’s role can not be ignored. Government guide and integrate this potential power. Infrastructure related to the creative industry needs to be equipped and cultural experts, writers, and academics need to be involved. It is they who have the creativity and can produce cultural content in the era of the creative economy. Keywords: creative economy, cultural content, infrastructure, govern